Augmented reality to facilitate students’ biology mastering concepts and digital literacy - Nurhasanah, Zakia; Widodo, Ari; Riandi, R. (JPBI (Jurnal Pendidikan Biologi Indonesia), 2019)
As one of abstract concepts, nervous system requires proper media which can represent the real condition. The purpose of this study was to observe the effect of augmented reality (AR) on students? mastering concept and digital literacy in biology. This quasi-experimental research was designed using non-equivalent control group design in which the instruments were test and questionnaire. The data were analyzed using independent samples t-test. The results indicated that AR gave significant positive effect on students? mastering concept. However, as it has no the same effect to students? digital literacy, the further observation to be done to ensure the undergirding reason behind the phenomena.